Privación de la libertad y centros carcelarios dese una perspectiva comparada (2015)
In this case, for both laws, the right to freedom is constituted as one of the main fundamental rights, the goal then this article will reflect on the deprivation of liberty of individuals who commit criminal acts and how the performance and warranties in the prisons is for these people